Application of Smart Healthcare in Comparative Analysis of Effect of Early External Fixator and Plate Internal Fixation Treatment on Postoperative Complications and Lower Limb Function Recovery of Patients With Unstable Pelvic Fracture - Hongwei Zhang; Fang Sun; Yao Li (Frontiers in Public Health, 2022)
ObjectiveTo comparatively analyze the effect of early external fixator and plate internal fixation treatment on postoperative complications and lower limb function recovery of patients with unstable pelvic fracture based on smart healthcare.MethodsThe clinical data of 98 patients with unstable pelvic fractures treated in our hospital from August 2018 to August 2021 were collected for retrospective analysis, and the patients were split into group A (plate internal fixation, n = 49) and group B (early external fixator treatment, n = 49) according to the surgical modalities. The time of operation, intraoperative blood loss, postoperative complications, etc. were compared between the two groups.ResultsBetween the two groups, group B had significantly better clinical indicators (P < 0.001), a greatly higher good rate of fracture reduction and postoperative Harris score (P < 0.05), and obviously lower VAS score and total incidence rate of postoperative complications (P < 0.05).ConclusionThrough the analysis based on smart healthcare, it is found that compared with plate internal fixation treatment, early external fixator treatment presents a better effect in treating patients with unstable pelvic fracture, because it is a reliable method to accelerate fracture healing, reduce postoperative complications, and improve lower limb function.